Methods of test for sodium tripolyphosphate (pentasodium triphosphate) and sodium pyrophosphate (tetrasodium pyrophosphate) for industrial use. Condensed phosphates for industrial use (including foodstuffs) - determination of oxides of nitrogen content - 3, 4-xylenol spectrophotometric method Part 15, (30th November 1982) - British Standards Institution,
No abstract available